An in vitro Model for Studying Breast Cancer Invasiveness in Response to Chemotherapy - Sharko, Vira; Pérez-García, Andrea; Mármol, Inés (Jornada de Jóvenes Investigadores del I3A, 2024)
This work aims to develop an in vitro three-dimensional model of triple negative breast cancer to study the influence of tumor microenvironment on treatment response and cell invasion. The model was exposed to chemotherapeutic agents and different responses to treatment were observed when cells were cultured on 2D or 3D.